An exploratory study of cultural understanding in English as a Foreign Language (EFL) reading in Argentina - Porto, Melina (2011)
Fil: Porto, Melina. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación; Argentina.